Pengaruh Pemberian Kombinasi Ekstrak Air Akar Kucing (Acalypha indica Linn.) dengan Ekstrak Etanol 70% Rimpang Jahe Merah (Zingiber officinale Rosc.) Terhadap Penurunan Kadar Asam Urat Tikus Putih - Saputri, Anita Ayu Dwi Ajie; Amin, Juheini; Azizahwati, Azizahwati (UI Scholars Hub, 2011)
Hyperuricemia treatment can be given roots of Acalypha indica Linn. Combined with red ginger plant (Zingiber officinale Rosc.) as anti-inflammatory drug. This study aimed to examine the effect of aqueous extract the roots of Acalypha indica Linn. with 70%ethanol extract of rhizome of Red Ginger from the decrease in blood uric acid levels of male rats made hiperurisemia by potassium oxonate. There were 35 male white rats of Sprague Dawley strain weighing 180 g to 200 gs were divided into seven groups. Three groups were given a combination of extract, consist of a fixed dose 5.4 g/200 g bb of Acalypha indica L. was combined with varied dose of red ginger, respectively 14 mg/200 g bb, 28 mg/200 g bb, and 56 mg / 200 g bb suspended with 0.5% CMC solution. Another groups consisted of a single dosage 5.4 g/200 g bb comparative of Acalypha indica Linn, allopurinol comparison, control induction, and normal controls were administered orally for eight days.Measurement of uric acid levels in blood plasma by enzymatic colorimetric method on UV-VIS spectrophotometer with a wavelength 520 nm. The results showed that the combination 5.4 g/200 g aqueous extract the root of Acalypha indica Linn with 56 mg/200 g red ginger might decrease uric acid levels equivalent to allopurinol and normal controls.